The last Tudor - Gregory, Philippa (New York : Touchstone, 2017)
Lady Jane Grey and her two sisters each dared to defy their queen. Seventeen-year-old Jane Grey was only queen of England for nine days before Queen Mary sent her to the executioner's block. Her younger sister, Katherine, heir to the insecure and infertile Queen Mary and then to her sister Queen Elizabeth, faced imprisonment in the Tower when her pregnancy betrayed her secret marriage. Mary, the youngest Grey sister and a beautiful dwarf disregarded by the court, kept her own secrets, while avoiding Elizabeth's suspicious glare. What will happen when the last Tudor defies her ruthless and unforgiving cousin Queen Elizabeth?"--
Includes bibliographical references (pages 517-518).
105195
Keywords: Grey, Jane, -- Lady, -- 1537-1554 -- Fiction; Hertford, Katherine Seymour, -- Countess of, -- 1540-1568 -- Fiction; Grey, Mary, -- Lady, -- 1545-1578 -- Fiction; 1485-1603; Queens -- Great Britain -- Fiction; FICTION / Historical; FICTION / General; FICTION / Suspense; Kings and rulers -- Succession; Great Britain -- Kings and rulers -- Succession -- Fiction; Great Britain -- History -- Tudors, 1485-1603 -- Fiction; Biographical fiction; Historical fiction; Biographical fiction